Exploring senior high school students’ preconceptions of collision concepts using visual representation - Ramdani, Rida; Nurahman, Arip (Insitut Pendidikan Indonesia, 2023)
Understanding students’ preconceptions is an important initial step towards meaningful and appropriate physics learning. Particularly in the concept of collisions, students’ understanding of collision concepts often does not align with those established by scientists. Therefore, to explore students’ preconceptions, visual representation enables students to connect their experiences with specific concepts. This aids in revealing and diagnosing students’ preconceptions. This research aims to analyze high school students’ preconceptions regarding collision concepts by examining their visual representations. The research design employs a qualitative descriptive research design with data collection methods including observation sheets and interviews. Observation sheets containing visual representations by students are analyzed using a four-step semiotic analysis approach, while interview data is analyzed thematically. Seventy-two tenth-grade students were sampled offline using convenience sampling. The research findings reveal that students’ use of visual representations indicates diverse preconceptions about collision concepts, categorizing them at the macroscopic level. This data is examined across four categories of student visuals: (1) 11 visuals that are correct; (2) 18 visuals based on the objects used; (3) 34 visuals depicting different types of collisions; (4) and 29 visuals that are incorrect.